Acute pancreatitis due to methanol toxicity during the COVID‐19 pandemic - Sadeghi, Mahdieh; Zakariaei, Zakaria; Fakhar, Mahdi; Tabaripour, Rabeeh; Banimostafavi, Elham Sadat; Azadeh, Hossien (Clinical case reports, 2021)
Acute methanol poisoning may be associated with a variety of symptoms, such as abdominal pain, blurred vision, loss of consciousness, and acute pancreatitis. We present a 37‐year‐old man with acute pancreatitis due to methanol poisoning during the COVID‐19 pandemic. Acute methanol poisoning may be associated with a variety of symptoms, such as abdominal pain, blurred vision, loss of consciousness, and acute pancreatitis. It should be noted that early management of methanol poisoning could prevent serious complications.